Identifying the factors that influence teacher practice change in a single case study. Issue 4 (2nd October 2019) - Forrest, Rachel; Lowe, Rachael; Potts, Michelle; Poyser, Chloe
ABSTRACT: To ensure improved educational outcomes for children and young people, it is essential that teachers adapt and change their teaching practice in accordance with new and emerging pedagogies and techniques. Despite its importance, many teachers find changing their practice a challenge, and this study sought to determine the factors that contribute towards teacher practice change. Using a realistic evaluation design, two participants were interviewed to identify factors which facilitated or inhibited teacher practice change in a primary school. Following interviews, a theory led data analysis was conducted to explore the context, mechanisms and outcomes that impacted on teacher practice change. The analysis showed that, in this situation, collaboration, reflection and knowledge of outcomes had an impact in facilitating teacher practice change. This research has implications for educational psychologists [EPs] who may utilise these factors when attempting to implement change for children and young people.